2021
DOI: 10.12688/f1000research.53689.3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with knowledge, attitudes and preventive practices towards COVID-19 in health care professionals in Lima, Peru

Abstract: Background: Nowadays, we are facing a disease caused by SARS-CoV- 2, known globally as COVID-19, which is considered a threat to global health due to its high contagiousness and rapid spread. Methods: Analytical cross-sectional study in 302 health professionals. An online questionnaire consisting of questions about knowledge, attitudes and practices (KAP) towards COVID-19 was applied. Socio- demographic, occupational and comorbidities factors were explored. Simple and multiple logistic regression models were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
3
6
0
Order By: Relevance
“…This was consistent with similar studies conducted in China, Egypt, Vietnam, Pakistan, Uganda, Iran, and Nigeria that showed that health care workers had a high level of knowledge about COVID-19 [2,17,21,26,33,37,43]. Nevertheless, other studies have reported a low level of knowledge among health care professionals [9,30].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This was consistent with similar studies conducted in China, Egypt, Vietnam, Pakistan, Uganda, Iran, and Nigeria that showed that health care workers had a high level of knowledge about COVID-19 [2,17,21,26,33,37,43]. Nevertheless, other studies have reported a low level of knowledge among health care professionals [9,30].…”
Section: Discussionsupporting
confidence: 90%
“…This study showed, in line with Zhang et al [43], the association between the level of COVID-19 practice and their working time. In summary, knowledge may lead to better practices [30,35] but could not be considered as the driver of health workers attitudes and behaviors. Thus, policy makers need not to rely only on COVID-19 continuing education programs [14] to change the attitudes and behaviours of health workers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution of scores by smoking status is described in Fig 3 . The lowest scores were recorded among students who use chicha (33 [27-39]), E cigarette (35 [31][32][33][34][35][36][37][38][39][40]) and especially those who use several forms of tobacco at the same time (31 [23-38.5]).…”
Section: Resultsmentioning
confidence: 99%